Development and validation of a measure of maladaptive social-evaluative beliefs characteristic of social anxiety disorder in youth: The Report of Youth Social Cognitions (RYSC) - Wong, QJJ; Certoma, SP; McLellan, LF; Halldorsson, B; Reyes, N; Boulton, K; Hudson, JL; Rapee, RM (American Psychological Association, 2018)
Recent research has started to examine the applicability of influential adult models of the maintenance of social anxiety disorder (SAD) to youth. This research is limited by the lack of psychometrically validated measures of underlying constructs that are developmentally appropriate for youth. One key construct in adult models of SAD is maladaptive social-evaluative beliefs. The current study aimed to develop and validate a measure of these beliefs in youth, known as the Report of Youth Social Cognitions (RYSC). The RYSC was developed with a clinical sample of youth with anxiety disorders (N = 180) and cross-validated in a community sample of youth (N = 305). In the clinical sample, the RYSC exhibited a 3-factor structure (negative evaluation, revealing self, and positive impression factors), good internal consistency, and construct validity. In the community sample, the 3-factor structure and the internal consistency of the RYSC were replicated, but the test of construct validity showed that the RYSC had similarly strong associations with social anxiety and depressed affect. The RYSC had good test-retest reliability overall, although the revealing self subscale showed lower temporal stability which improved when only older participants were considered (age ≥9 years). The RYSC in general was also shown to discriminate between youth with and without SAD although the revealing self subscale again performed suboptimally but improved when only older participants were considered. These findings provide psychometric support for the RYSC and justifies its use with youth in research and clinical settings requiring the assessment of maladaptive social-evaluative beliefs. (PsycINFO Database Record